(untitled) (Journal of Imam Al-Kadhim College, 2023)
The research aims to monitor the overlap between classical and colloquial Arabic, and then establish a comprehensive linguistic renaissance to meet the requirements of the era in which we live, while preserving the originality and beauty of the Arabic language. This requires all the institutions of society to take a serious stand, as Arabic is an essential part of our dear Arab and Islamic identity, and any waiver of it is considered a waiver of our originality. Perhaps the observer will notice that our societies are experiencing conflict and a marked aversion to the use of classical Arabic. The dry methods used in teaching the Arabic language in the various educational stages led to a move away from the classical expression and the preference for the colloquial expression, which linked the use of the classical language to the limited and historical, and in light of this, the research tries to shed light on the reasons behind this, are the curricula or the teachers of the Arabic language? Or a lack of interest in linking theoretical lessons to easy and fun educational applications? Facilitates the goal of language learning and young people love it.